2020
DOI: 10.1212/wnl.0000000000010013
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of Alzheimer disease

Abstract: Objective:Evidence from observational studies for the effect of physical activity on the risk of Alzheimer’s disease (AD) is inconclusive. We performed a two-sample Mendelian randomization analysis to examine whether physical activity is protective for AD.Methods:Summary data of genome-wide association studies on physical activity and AD were used. The primary study population included 21,982 AD cases and 41,944 cognitively normal controls. Eight single nucleotide polymorphisms (SNPs) known at P<5x10-8 to b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
11
1
Order By: Relevance
“…Our results were contradictory to a previous MR study which suggested that physical activity did not affect the risk of development of AD 66 . The possible reason might be as follows: previous MR studies used moderateto-vigorous physical activity (MET ≥ 6) as exposure, which might be different from the effects of daily activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results were contradictory to a previous MR study which suggested that physical activity did not affect the risk of development of AD 66 . The possible reason might be as follows: previous MR studies used moderateto-vigorous physical activity (MET ≥ 6) as exposure, which might be different from the effects of daily activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Thirdly, the influence of confounding factors on the studied association was reduced due to the strict selection of IVs. Fourthly, the previous MR analysis used average accelerations and the fraction of accelerations > 425 milligravities as exposure measures, the latter meaning vigorous physical activity (METs ≥ 6) only 66 . More physical activity statuses were analyzed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The few available Mendelian randomizations investigating the relation between physical activity and cognition or Alzheimer's disease have shown mixed results. Mendelian randomization studies investigating the relation between genetically predicted physical activity and the risk of Alzheimer's disease have reported no evidence for a causal association [78,79], or increased odds of developing Alzheimer's disease for those with a higher genetic liability of engagement in moderate intensity physical activity [80]. In the only Mendelian randomization study investigating the relation between physical activity and and depression are major confounders when studying the relation between physical activity and executive function.…”
Section: Discussionmentioning
confidence: 99%
“…In support of these (non-MR) findings, MR has uncovered a causal protective effect of vigorous physical activity on myocardial infarction (Zhuo et al, 2021) and coronary artery disease (Zhuang et al, 2020) in Europeans, although no effect on other cardiovascular phenotypes such as heart failure, atrial fibrillation or ischemic stroke has been detected by further MR studies (Bahls et al, 2021;van Oort et al, 2020). Additionally, walking time was found to protect against Alzheimer disease in one MR study (Zhang et al, 2022), but no associations with accelerometer-measured physical activity were reported in others (Baumeister et al, 2020;Wu et al, 2021) (Supplementary Figure 4).…”
Section: Sedentarismmentioning
confidence: 96%
“…Diagram for the MR analysis of the effect of physical activity on a number of cardiovascular phenotypes and Alzheimer disease. Based on Bahls et al (2021), Baumeister et al (2020). van Oort et al (2020), Wu et al (2021), Zhang et al (2022), Zhuang et al (2020), and Zhuo et al (2021).…”
mentioning
confidence: 99%